1994
DOI: 10.1007/s004410050214
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and histochemical evidence for the presence of noradrenaline, serotonin and gamma-aminobutyric acid in chief cells of the mouse carotid body

Abstract: The immunohistochemical study revealed tyrosine hydroxylase (TH), dopamine beta-hydroxylase (DBH), phenylethanolamine N-methyltransferase (PNMT), serotonin, glutamate decarboxylase (GAD) and gamma-aminobutyric acid (GABA) immunoreactivities in the mouse carotid body. TH and DBH immunoreactivities were found in almost all chief cells and a few ganglion cells, and in relatively numerous varicose nerve fibers of the carotid body. The histofluorescence microscopy showed catecholamine fluorescence in almost all chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 0 publications
1
22
1
Order By: Relevance
“…In contrast to the mouse [13,15], we noted a small number of chemoreceptor cells containing, mostly discrete, GABA immunoreactivities.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…In contrast to the mouse [13,15], we noted a small number of chemoreceptor cells containing, mostly discrete, GABA immunoreactivities.…”
Section: Discussioncontrasting
confidence: 87%
“…To our knowledge, this demonstration is second to that in the mouse [13,15] that shows GABA in the mammalian carotid body. Distribution of the immunoreactivities we found in the cat is in overall accord with that reported in the mouse, where they were revealed both in the cytoplasm and in the dense-core vesicles [13].…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Abnormalties in glomus cells of the A/J mice were also apparent in immunocytochemistry for TH. The presence of TH in glomus cells is well known in several species (18,26,39) including mice (27), and, therefore, we used TH as a marker for glomus cells. We observed typical TH immunostaining in the carotid body of the DBA/2J mice.…”
Section: Discussionmentioning
confidence: 99%
“…According to studies with inhibitory neurotransmitters, it has been reported that dopamine is present at high concentrations in the glomus cells (Gonzalez et al 1994). Immunohistochemically, immunoreactivity for tyrosine hydroxylase (TH; EC1.14.16.2), the rate-limiting enzyme of catecholamine biosynthesis, was widely observed in the glomus cells (Wang et al 1991;Oomori et al 1994;Wang and Bisgard 2002). Additionally, it is reported that dopamine D 2 receptor mRNA is expressed in glomus cells of rat carotid body in a study using ISH (Czyzyk-Krzeska et al 1992b), and that immunoreactivity for dopamine D 2 receptor was observed in glomus cells and nerve fiber of human carotid body (Lazarov et al 2009).…”
mentioning
confidence: 99%